2017
DOI: 10.1016/j.brainres.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Increased contextual cue utilization with tDCS over the prefrontal cortex during a recognition task

Abstract: The precise role of the prefrontal and posterior parietal cortices in recognition performance remains controversial, with questions about whether these regions contribute to recognition via the availability of mnemonic evidence or via decision biases and retrieval orientation. Here we used an explicit memory cueing paradigm, whereby external cues probabilistically predict upcoming memoranda as old or new, in our case with 75% validity, and these cues affect recognition decision biases in the direction of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 92 publications
(131 reference statements)
1
4
0
Order By: Relevance
“…At the end of the stimulation session, the current was again ramped up to 2 mA over 30 seconds. This procedure is commonly used to blind participants in TES studies 27,58,59 . For the first five minutes of stimulation, subjects were asked to relax and let their mind wander.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the stimulation session, the current was again ramped up to 2 mA over 30 seconds. This procedure is commonly used to blind participants in TES studies 27,58,59 . For the first five minutes of stimulation, subjects were asked to relax and let their mind wander.…”
Section: Methodsmentioning
confidence: 99%
“…One study reported that anodal tDCS applied to left anterior temporal lobe can decrease false alarms for semantically related lures (Boggio et al, 2009 ), whilst another reported a decrease in false alarms for associative, but not semantically related lures (Díez et al, 2017 ). Other studies showed an increase in hits (i.e., correct yes responses to probes) when targeting the parietal cortex with a bilateral montage (i.e., right-anodal/left-cathodal), whilst the opposite montage (i.e., left-anodal/right cathodal) increased false alarms (see Pergolizzi and Chua, 2015 , 2016 ; but see also, Pergolizzi and Chua, 2017 ).…”
Section: Introductionmentioning
confidence: 91%
“…This was interpreted as evidence of direct frontoparietal involvement in processing location-based regularities. These results aligned with two other stimulation studies that looked at target-context processing in contextual cuing that argued for a direct role of the frontal cortex (Pergolizzi & Chua, 2017;Zinchenko, Conci, Taylor, Müller, & Geyer, 2019).…”
Section: Brain Stimulation Effects On Statistical Learningsupporting
confidence: 87%